An investigation into the construction industry's view on fire prevention in high-rise buildings post Grenfell. Issue 3 (12th November 2019) - Mohamed, Iman Farah; Edwards, David John; Mateo-Garcia, Monica; Costin, Glenn; Thwala, Wellington Didibhuku Didibhuku
Abstract : Purpose: The purpose of this paper is to explore contemporary attitudes amongst UK construction professionals regards fire safety post the Grenfell Tower disaster. Specifically, the research examines practitioner's perceptions of fire safety design, material specification, construction and maintenance of high-rise blocks throughout a building's whole life cycle. Design/methodology/approach: A multi-methodology approach was adopted that utilises a mix of research methods. Extant literature and media content is used as a secondary data source, providing a more insightful interpretivist analysis – the results of which guided the development of the survey's main question set. Primary survey data are sourced from structured interviews and questionnaires completed by participating industry professionals and built environment undergraduate students using non-representative sampling methods. In addition, a Grenfell Tower special advisory panel member was interviewed to add further validity to the overall findings. Findings: The quantitative findings present evidence to suggest that the Grenfell disaster (and media storm that has surrounded this event) has raised the general level of fire safety knowledge and competency amongst construction professionals. However, qualitative feedback from the special advisory panel member suggests specific fire prevention knowledge remains elusive within both industry and taught programmes at Higher Education Institutes. As a consequence, changes in the taught curriculum are proposed together with an extension of the role of facilities managers in practice to cover fire safety in greater depth. Originality/value: This paper provides thoughtful insights into the contemporary discourse on fire safety within the UK construction industry. The research also provides critical suggestions to both industry and policy makers which seek to prevent a repeat tragedy occurring again.